The UNIDROIT principles on international commercial contracts and the effects derived from Covid-19 on contract relations: a perspective from the Spanish Law - Díez Soto, Carlos Manuel; González Pacanowska, Isabel Victoria (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
The Note published on July 15th 2020 by the Unidroit Secretariat on the Unidroit Principles of International Commercial Contracts and the Covid-19 health crisis seeks to offer guidance on how the Principles could help as a useful tool to address the main contractual disruptions caused by the pandemic and by the measures taken to mitigate its effects, as well as the ensuing economic crisis. The magnitude of the crisis undoubtedly demands specific legal measures, inspired by criteria of distributive justice (and not just commutative). It is also a question of preventing an overwhelming burden of the justice system, as well as the drawbacks of criteria disparities and the unavoidable slowness in the development of consolidated jurisprudential guidelines. Emergency legislation, however, will not be able to provide satisfactory solutions to all the conflicts that have arisen and will continue to arise in the near future, and it is in this area where general concepts will have to be used. The Note provides interesting insights into the interpretation and application of national rules governing the basic institutions of obligations and contracts, in particular those related to the notions of force majeure/fortuitous event, impossibility and hardship/rebus sic stantibus. In this article, following the same structure as the Note itself, the focus is not so much on emergency legislation, but rather on the way in which both the Principles and the suggestions of the Note can be used in order to propose possible solutions in the context of the Spanish legal system, taking into account the evolution of caselaw, especially of recent years, and the understanding of the notions of force majeure and fortuitous case, impossibility, hardship, as well as the scope, the requirements and the effects of the rebus rule.